2021
DOI: 10.1177/08853282211025781
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological performances of a semi-resorbable barrier membrane based on silk fibroin-glycerol-fish collagen material for guided bone regeneration

Abstract: The fragility of silk fibroin film is a drawback to being used as a barrier membrane. Semi-resorbable barrier membranes maintain function longer than a resorbable membrane and no need to be removed. The study aimed to fabricate semi-resorbable membranes using silk fibroin with glycerol plasticizer (Group A), immobilized with fish collagen (Group B), and then characterized, in vitro biocompatibility tested, and compared with a commercial collagen membrane (Group C). Group B showed more roughness (0.2155 µm) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Silk fibroin (SF) biomaterials are promising bone regenerative matrices due to the biocompatibility, excellent and tunable mechanical properties, and ease of materials fabrication [ [9] , [10] , [11] , [12] ]. SF-based scaffolds, films and hydrogels have been developed to repair various bone defects [ 9 , [13] , [14] , [15] ]. The cytocompatibility and bioactivity of these matrices were further improved by changing nano-micro structures, anisotropic topography, degradation behavior and mechanical performance [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF) biomaterials are promising bone regenerative matrices due to the biocompatibility, excellent and tunable mechanical properties, and ease of materials fabrication [ [9] , [10] , [11] , [12] ]. SF-based scaffolds, films and hydrogels have been developed to repair various bone defects [ 9 , [13] , [14] , [15] ]. The cytocompatibility and bioactivity of these matrices were further improved by changing nano-micro structures, anisotropic topography, degradation behavior and mechanical performance [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics were consistent with the hydrophobicity of membranes. 20 The OD from the 2D digital radiograph at 4-weeks of the BG group was lower than the E group, but not statistically different, this might be the consequence of the collapse of the collagen membrane into the defect area and interrupted the bone formation in the early stage.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, silk fibroin and fish collagen-based materials with a glycerol plasticizer had been fabricated and characterized to overcome the brittleness and low mechanical strength of silk fibroin material for a barrier membrane and to diminish religious restrictions from the mammal sources. 20 The in vitro study showed that the silk fibroin-glycerol and silk fibroin-glycerol-collagen membranes had good physical and mechanical properties with high stiffness 1.5–2.2 times that of the collagen membrane but still yielded sufficient elongation when compared to the collagen membrane, particularly the silk fibroin-glycerol-collagen. 20 The constructed membrane does not easily collapse, so it can maintain space for bone regeneration with slow resorption and has good biocompatibility to promote cell viability and cell proliferation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Figure a, the film has a specific stability and can maintain the film morphology for 3 days under the environment of 22 °C and RH = 66% and gelatinize on the 6th day. This behavior is due to the dual role of calcium ion’s excellent water molecule capture properties it can capture water molecules from the air , and glycerin’s water-retaining function making the composites gelled. When the gel material was attached to the glove to detect electrical signals from a finger bending, more sensitive resistive signals were found.…”
Section: Resultsmentioning
confidence: 99%